Faktor – Faktor yang Mempengaruhi Ketidakberhasilan ASI Eksklusif pada Ibu Menyusui - Prihatini, Frila Juniar; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
The failure of exclusive breastfeeding is a common occurrence in Indonesia, despite the government's recommendation for exclusive breastfeeding. This study aims to identify the risk factors for the failure of exclusive breastfeeding. This research utilized a literature review or literature study using a descriptive method. The literature search was conducted through publications in two databases, PubMed and Google Scholar. A strategic search method was employed to obtain journals using the keywords "Factors influencing the failure of exclusive breastfeeding." The inclusion criteria used were journals that discussed factors influencing the failure of exclusive breastfeeding in breastfeeding mothers and were accessible in full text. The journal timeframe was limited to 2017-2023. From the search results: the researcher found 413 articles using PubMed and 6,220 articles using Google Scholar that matched the keywords. Out of those, 10 articles were found that met the criteria and could be used in the literature review. The risk factors for the failure of exclusive breastfeeding are unsupportive spouses, giving birth in primary healthcare facilities, and receiving misinformation from healthcare provider.